Comparative Cytogenetic Study on Male and Female Captive Sumatran Elephant in Elephant Training Center, Way Kambas National Park - Priyambodo Priyambodo; Elly L. Rustiati (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
Sumatran elephant (Elephas maximus sumatranus) was one of five big mammals in Way Kambas National Park (WKNP). Cytogenetic study was a part of conservation effort for sumatran elephant, especially in conservation genetic field. Captive sumatran elephant’s blood in Elephant Training Center (ETC) WKNP was collected to karyotype analysis. Captive sumatran elephant’s chromosome was analyzed by squashing technique with pretreating cells in a hypotonic solution. The study of karyotypes were made by giemsa staining applied to captive elephant’s blood cell. The diploid number of captive sumatran elephant was 56 both in male and female. The karyotype analysis performed different fundamental number in male and female, both of total fundamental number (FN) and autosomal fundamental number (FNa). Chromosome of female sumatran elephant showed the FN = 8, and FNa = 6, but in male sumatran elephant FN = 7, and FNa = . The karyotypes of X chromosome was large submetacentric and Y chromosome was small acrocentric.. The karyotype presented here will compilled with DNA fingerprinting analysis of all captive sumatran elephant in ETC WKNP as references in future breeding policy.